The Treatment of Polluted Water by Heavy Metals in Maysan Governorate by Phytoremediation - Qadoori, Ayman H. (Iraqi Journal of Science, 2025)
The environmental difficulties faced by Iraqi society, particularly in the countryside, worsen over time due to a lack of interest in environmental duties caused by a lack of awareness of the environmental risk. At a time when oil companies sought Iraqi government approval to invest in and develop Iraqi oil fields, particularly in the south of Iraq, heavy metals emerged as one of the most visible pollutants associated with the oil industry as by-products of oil extraction operations. Therefore, the environment is exposed to gradual demolitions that directly affect biodiversity and deteriorate water quality in the region. Consequently, it became necessary to find environmentally friendly treatment methods from the elements of the environment itself. Hence, the phytoremediation method was ideal for solving some pollution problems in the southern regions of Iraq, specifically the Iraqi marshes. This research discusses the impact of the most prominent heavy metals polluting the waters of Umm Al-Na'aj Pond and Al-Hawizeh marshland, proposes two methods for phytoremediation, and shows the efficiency of each of them in the adsorption of heavy metal pollutants.